The Influence of Leadership and Work Motivation on Employee Performance at the Urban Village Office of Solok City - Husain, Faiz Muhammad; Yeni, Afni; Sriyanti, Esi (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
This study aims to determine the influence of Leadership and Work Motivation on Employee Performance at the Lurah Office in Solok City. A quantitative method was employed, involving a sample of 106 respondents. The results of the statistical analysis indicate that Leadership partially has no significant effect on Employee Performance, as evidenced by the t-test value (tcount 1,565 < ttable 1,983) with a significance value of 0.121 > 0.05. Conversely, Work Motivation partially has a significant effect on Employee Performance, as demonstrated by the t-test value (tcount 6,561 > ttable 1,983) and a significance value of 0.000 < 0.05. Furthermore, the study concludes that Leadership and Work Motivation simultaneously influence Employee Performance at the Lurah Office in Solok City. This is supported by the F-test results (fcount 55,941 > ftable 3,058) with a significance level of 0.000, which is considerably lower than alpha (0.05). The R-Square value was found to be 0.521, indicating that these variables contribute 52.1% to Employee Performance, while the remaining 47.9% is influenced by other variables not included in this study.